"I've Lost My Callouses:" A Phenomenological Investigation of Music Therapists Who Left the Profession. (30th March 2023) - Silverman, Michael J; Segall, Lorna E; Edmonds, Theo
Abstract: Although changing industries is common for many professionals, there is a lack of research regarding why music therapists have left the profession. The purpose of this phenomenological investigation was to explore why music therapists in the United States left the profession and understand how music therapy academic and clinical training might be applied across a range of occupational opportunities. We interviewed eight music therapists who had worked in and left the profession for employment in other industries. We used interpretative phenomenological analysis to analyze transcripts and incorporated member checking and trustworthiness to verify our findings. The first theme described how there were multiple factors that contributed to the decision to leave the music therapy profession. The second theme described how participants grappled with the decision to leave the music therapy profession. Regarding why music therapists left the profession and how their education and training were related to their new industry, we used a modified social ecological model to depict four superordinate themes (supported by 11 themes) that described (1) individual and interpersonal factors contributing to the need for occupational change; (2) music therapy skills that facilitated occupational change; (3) unmet professional expectations that contributed to occupational change; and (4) desired changes to the music therapy curriculum for greater career flexibility. Constituting an idiosyncratic process for each participant, leaving the music therapy profession was a complex and multifaceted phenomenon. Implications for education and greater career flexibility, limitations of the study, and suggestions for future research are provided.